Sosialisasi Perancangan Perjanjian Pengelolaan Hutan di Desa Giri Sekar, Kecamatan Panggang, Gunungkidul, DIY: Sebuah Program Pengabdian kepada Masyarakat Berbasis Hukum Lingkungan dan Agraria - Fakultas Hukum Universitas Negeri Surabaya; Heppy Hyma Puspytasari; Astrid Amidiaputri Hasyyati; Meita Debi Riyanti; Erma Zahro Noor (Jurnal Darma Loka, 2025)
Village forest management in Indonesia often faces challenges related to legal certainty, benefit distribution, and environmental sustainability. Giri Sekar Village, Panggang District, Gunungkidul Regency, is an area with community forest potential but also ecological vulnerability due to its karst landscape. Through the Community Service (PkM) program, a team of academics conducted a socialization program on the drafting of forest management agreements, fulfilling the academic obligations of the Tri Dharma of Higher Education. Giri Sekar Village has significant community forest potential but faces challenges in legal certainty and environmental preservation. Giri Sekar Village has significant community forest potential but faces challenges in legal certainty and environmental preservation. This socialization program aimed to improve community legal understanding, strengthen citizen participation, and foster community understanding of the contents of the draft agreement, which can serve as a legal basis for forest management. Through group discussions, outreach, and training, this activity successfully raised community legal awareness and created participatory agreement instruments. This contributed to improving community legal understanding and providing legal instruments that support sustainable forest governance.